2013
DOI: 10.3109/10428194.2013.769216
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of radiotherapy for primary intraocular non-Hodgkin lymphoma

Abstract: This study aimed to retrospectively evaluate the efficacy of radiotherapy for primary intraocular non-Hodgkin lymphoma (PIOL). Between May 1998 and October 2010, 22 immunocompetent patients (four men, 18 women; median age 70 years, range 53-79 years) were diagnosed with PIOL. Magnetic resonance imaging showed no intracranial involvement in any patient. Patients received radiotherapy at a median total dose of 30 Gy (range 30-40 Gy). Three-year overall survival, progression-free survival and local control rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…The literature regarding the treatment of isolated PVRL, including almost exclusively retrospective studies, remains controversial regarding the use of local, systemic or local and systemic treatment. Regarding ocular radiotherapy, Mikami et al and Teckie et al found brain relapse rates of 55% and 42%, respectively, in patients treated with ocular radiotherapy after a median follow‐up time of 36 and 25 months 18,19 . Berenbom et al showed that the addition of chemotherapy to ocular radiotherapy delayed the onset of brain relapse in patients: the median BFS was 28 months with chemotherapy versus 8 months without ( p = .24) 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature regarding the treatment of isolated PVRL, including almost exclusively retrospective studies, remains controversial regarding the use of local, systemic or local and systemic treatment. Regarding ocular radiotherapy, Mikami et al and Teckie et al found brain relapse rates of 55% and 42%, respectively, in patients treated with ocular radiotherapy after a median follow‐up time of 36 and 25 months 18,19 . Berenbom et al showed that the addition of chemotherapy to ocular radiotherapy delayed the onset of brain relapse in patients: the median BFS was 28 months with chemotherapy versus 8 months without ( p = .24) 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the European Association for Neuro‐Oncology stated that either local or systemic treatments could be options for PVRL treatment and that the decision should be made according to the individual risk of treatment toxicities and local expertise. Ocular radiotherapy and intravitreal chemotherapy are associated with good response rates and a variable rate of ocular relapse (0%‐61%) but do not seem to change the risk of secondary cerebral involvement and therefore overall survival 3,14‐19 . Systemic chemotherapy seems promising in the prevention of cerebral involvement, as reported in several recent studies, 8,15,20,21 but therapeutic options included in the systemic chemotherapy arm were very different, and data about IV HD‐MTX‐based chemotherapy are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Однако следует учитывать, что СРТ может сопровождаться ранними лучевыми реакциями (во время проведения СРТ или непосредственно после ее окончания) и чревата поздними осложнениями (сроки от 6 мес), которые могут стать различной причиной потери зрения. В литературе описаны следующие осложнения лучевой терапии опухолевых заболеваний глаза: к ранним реакциям относятся эритема кожи, отек век, конъюнктивит, снижение чувствительности роговицы и ее эпителиальные дефекты; к поздним осложнениям -симблефарон, синдром сухого глаза, помутнение роговицы с неоваскуляризацией, катаракта, неоваскулярная глаукома, ретинопатия, нейрооптикопатия [13][14][15][16] [10].…”
Section: Discussionunclassified
“…Было принято решение о проведении радиотерапии в рамках комбинированного лечения ПИОЛ или самостоятельного лечения в случае невозможности химиотерапии на первом этапе лечения. В зарубежной литературе [2,5,7,9,10] представлен опыт радиотерапии ПИОЛ. Так, R. Mikami и cоавт.…”
unclassified
“…Так, R. Mikami и cоавт. [10] сообщают о 22 иммунокомпетентных пациентах с ПИОЛ, которым проведена СРТ с СОД от 30,0 до 40,0 Гр. Авторы делают вывод, что в 81% наблюдений после СРТ отмечалось повышение зрительных функций или их стабилизация, у 5 пациентов сформировалась катаракта, и в целом в результате СРТ получен локальный контроль опухоли.…”
unclassified